1999
DOI: 10.1051/aas:1999521
|View full text |Cite
|
Sign up to set email alerts
|

The effective temperature scale of giant stars (F0–K5)

Abstract: Abstract. We present calibrations of the effective temperatures of giant stars versus [Fe/H] and colours (U. These calibrations are based on a large sample of field and globular cluster stars which roughly cover spectral types from F0 to K5. Their effective temperatures, scaled to direct T eff determinations via reliable angular diameter measurements, were derived by applying the infrared flux method. The empirical relations have been fitted to polynomials of the form θ eff = P (colour, [Fe/H]) by using the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,393
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 983 publications
(1,456 citation statements)
references
References 16 publications
50
1,393
13
Order By: Relevance
“…The temperatures were finally determined using V − K and the IRFM-based calibrations of Alonso et al (1999). The E(B − V) were downloaded from the IRSA webpage using the stellar IDs; we adopted the mean E(B − V) values from Schlegel et al (1998).…”
Section: Stellar Atmospheric Parameter Estimatesmentioning
confidence: 99%
“…The temperatures were finally determined using V − K and the IRFM-based calibrations of Alonso et al (1999). The E(B − V) were downloaded from the IRSA webpage using the stellar IDs; we adopted the mean E(B − V) values from Schlegel et al (1998).…”
Section: Stellar Atmospheric Parameter Estimatesmentioning
confidence: 99%
“…Using the calibrations of Alonso et al (1999) for HD 27536 and the Alonso et al (1996) calibrations for HD 216803 with the Strömgren indices found by Olsen (1993) in both cases assuming Solar metallicity. The uncertainties are around 120−140 K for all values.…”
Section: Temperature Gravity Microturbulencementioning
confidence: 99%
“…To take into account the effect of metallicity on the zero-point F (CI 0 ) st , we estimated the gradient dF (CI 0 ) st /d[F e/H] ≈ +0.24 from the calibrations by Alonso et al 1999, Sekiguchi & Fukugita 2000, Gonzalez Hernandez & Bonifacio 2009. In some cases (particularly for large-amplitude color variations) the "free" calibration, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The key point of our approach is that the values of function F are computed from the already available calibrations of the bolometric correction BC(CI 0 ) and the effective temperature logT (CI 0 ) (Flower 1996, Bessel, Castelli and Plez 1998, Alonso, Arribas and Martinez-Roger 1999, Sekiguchi and Fukugita 2000, Ramirez and Melendez 2005, Biazzo et al 2007, Gonzalez Hernandez and Bonifacio 2009. These calibrations are expressed as high-order power series in the intrinsic colour:…”
Section: Theoretical Backgroundmentioning
confidence: 99%